2014
DOI: 10.7243/2054-3425-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of lens luxation in the horse: visual outcomes

Abstract: Background: The purpose of this study was to describe the visual outcomes of surgical therapy for lens luxation/subluxation in the horse. Methods:The medical records of horses that had surgical correction of lens luxation/subluxation at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Some studies recommend PPV only in case of a positive ocular leptospiral test [5,11]. Other authors consider PPV also indicated in the case of previous uveitis with accumulation of inflammatory products or lens remnants in the vitreous [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies recommend PPV only in case of a positive ocular leptospiral test [5,11]. Other authors consider PPV also indicated in the case of previous uveitis with accumulation of inflammatory products or lens remnants in the vitreous [12][13][14].…”
Section: Introductionmentioning
confidence: 99%